Sales and market forecasting for entrepreneurs - Berry, Timothy; Safari eBooks (New York : Business Expert Press, 2010)
"This book, written by a 30-year veteran in planning, market research, and running a business, shows you how to educate your guesses with real world common sense, to make practical business forecasts, and to use them to manage your business better. While it goes through some of the more sophisticated techniques as well, its focus is on what people really use. The book includes cases, stories, examples, and real experience. Methodologies include customer poll, market share model, chain method, product life cycle, idea adoption, idea contagion, strategic interactive model, moving averages, weighting moving average, exponential smoothing, regression, and correlation. This is a book you'll use to run your business better"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Sales forecasting; Business forecasting; Sales management; Small business -- Management; Electronic books